BEYOND A GAME: PEER EDUCATION TO SEPARATE FOOTBALL AND VIOLENCE - Perihan Elif Ekmekci; Kumru Done; Berna Arda; Alp Burak Ekmekci (Informascope, 2018)
Football, one of the sports with roots in history, has been associated with violence and tragedy in various countries. Several studies have tried to understand the nature and structure of hooliganism and its common cross-national characteristics, severity, and causes. Although existing literature suggests a variety of strategies to prevent violence in football, it is widely accepted that there must be grassroots movements and self-awareness, besides these measures,to reduce cases of aggressionin football. This study, whichwas awardedthe Fair Play prize in 2014 by the Turkish Olympic Committee, focuses on training fans using the peer education methodology. The young fans of Beşiktaş Football Club implemented a peer education program and conducted an online survey to assess itseffectiveness and understand the participants' perceptions and reflections regarding the causes of and methods to preventfootball hooliganism.The results suggest that the training program was effective and that it should be disseminated to reach all other associations to achieve results that are more positive.